The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 06: Paris - Casanova, Giacomo, 1725-1798; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 06: Paris" is part of an autobiographical memoir written in French by the famous Venetian adventurer Giacomo Casanova. This volume chronicles a portion of Casanova's adventurous life through 1774, drawn from his massive 3,700-page manuscript. Originally censored and mistranslated for over a century, the true text remained hidden until the original French manuscript was finally published in its unexpurgated form, revealing the authentic voice of one of history's most notorious figures. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Histoire_de_ma_vie
Release date is 2004-12-10
Produced by David Widger
Keywords: Casanova, Giacomo, 1725-1798; Europe -- History -- 18th century -- Biography